A new error analysis technique for cooperative 5G systems. (November 2018) - Nagarajan, Velmurugan; Annadurai, Chinnamuthu
Abstract: Deployment of cooperative techniques on 5G cellular networks has been a subject of recent interest to researchers. A cooperative diversity relay system has a root terminal, an intermediate terminal and an end terminal is presented. The intermediate terminal detects the root terminal's information through the decode and forward protocol and forwards it to the end terminal. The authors have proposed a new switched diversity scheme for the above system and have done a mathematical investigation of its performance. In the flat Rayleigh fading environment with phase shift keying modulation, the symbol error probability has been derived for a cooperative diversity system. The proposed scheme has been compared against other competing schemes seen in literature. The numerical results have revealed a better performance of the proposed system than the existing system.